Chemical parameters of gourmet salts compared withsalt extracted from eichhornia crassipes evaluated by energy-dispersive x-ray spectrometry - Rossignoli, Paulo Afonso; Silva, Frederico Fonseca da; Peternella, Wilson Sacchi (Ciência e Natura, 2022)
Salts have been part of human nutrition since 2,000 b.C., having originated in the Zhongba region, in China. Itssubstantial availability in food markets and stores specialized in condiments led us, curiously, to compare its elemental chemical composition with that of salt extracted from a floating aquatic macrophyte, known commonly as “water hyacinth” (Eichhornia crassipes), whose product, after extraction from dry matter, was popularly denominated“indigenous salt”. The objective of the present study was to evaluate the chemical composition of gourmet salts in comparison with indigenous salt using the energy-dispersive X-ray spectrometry (EDX) technique. Eichhornia crassipes exhibited higher concentrations of chloride (35.834%), potassium (62.146%), sulfur (1.095%), calcium (0.450%), bromine (0.177%), silicon (0.124%), copper (0.029%), magnesium (0.123%), and rubidium (0.023%) than the gourmet salts. Our results indicate that this indigenous salt should be consumed under medical guidance due to its high concentration of potassium chloride, a salt whose properties are used for specific human treatment and not daily consumption.